Impact of Hostel Life on the Academic Performance of Students - Bibi, Wajeeha; Bibi, Amnaa; Khatoon, Bibi Asma (The Lighthouse Journal of Social Sciences, 2024)
The purpose of the current study is to investigate the impact of hostel life on students’ academic performance. The data (N=300), with balanced representation of both genders, was collected using a purposive sampling technique and quantitative research design from different hostels around Haripur city. Quantitative research design was applied to the current study. For measuring the study purpose, one scale was used: the Academic Performance Scale (APS), a 5-point Lickert scale with 8 items. Results show that hostel life negatively impacts the academic performance of intermediate compared to undergraduate students. Findings also indicate a mean difference in academic performance between male and female hostel students. Additionally, there is no significant difference between high and middle Socioeconomic Status (SES), while a low significance difference is observed with low SES. These study findings have significant implications for educational psychology and social psychology. Suggestions and limitations are provided for future research.